There's Nothing Like an English Summer, Is There? Except an English Winter. Downton Abbey, a British Cult Tv Series and Its Fandom (Cinéma & Cie. Film and Media Studies Journal, 2012)
The British TV show Downton Abbey is a significant case – with its unprecedented and unexpected worldwide success – in a more general evaluation of the contemporary media environment, and of European TV productions in particular. This article explores the Downton Abbey “phenomenon” through a survey of its fans’ online activities. The first introductory part of this essay focuses on the concept of Cult TV Show and its possible application to this peculiar product. The second part extensively discusses Downton Abbey fans’ online activities, monitored from August to September 2012. This part is focused on five different factors of the series identified as those that mainly raised the interest and approval of the fans. Finally, the last part of this article draws some conclusions about the global nature of Downton Abbey fandom and about the series status as “mainstream cult.”